2011
DOI: 10.1108/14676371111118200
|View full text |Cite
|
Sign up to set email alerts
|

College and university dining services administrators' intention to adopt sustainable practices

Abstract: This study examined college and university dining services administrators' (CUDSAs) intention to adopt sustainable practices. The theory of planned behavior (TPB) including constructs of subjective norm, attitude, perceived behavior control, and personal norm, formed the theoretical framework. A web-based questionnaire was developed, pretested, and distributed to 535 CUDSAs in the U.S.A. Results indicated that subjective norm (pressure from others) had the most influence on CUDSAs' intention to adopt sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 41 publications
4
41
1
Order By: Relevance
“…Although the TPB has been tested on ecological behavior in one's personal life (Harland, Staats, & Wilke, 1999;Kaiser & Gutscher, 2003), only one study, conducted with college and university foodservice directors, applied the TPB to sustainable practice decisions by foodservice directors in their operations. Those results, reported by Chen, Gregoire, Arendt, and Shelley (2011), suggested that subjective norm and attitude toward sustainable practices had the greatest influence on intention to adopt sustainable practices in the future.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Although the TPB has been tested on ecological behavior in one's personal life (Harland, Staats, & Wilke, 1999;Kaiser & Gutscher, 2003), only one study, conducted with college and university foodservice directors, applied the TPB to sustainable practice decisions by foodservice directors in their operations. Those results, reported by Chen, Gregoire, Arendt, and Shelley (2011), suggested that subjective norm and attitude toward sustainable practices had the greatest influence on intention to adopt sustainable practices in the future.…”
Section: Introductionsupporting
confidence: 54%
“…Eight dietetics program faculty and hospital foodservice managers served as an expert panel to review the questionnaire to assure questions used by Chen et al (2010Chen et al ( , 2011 for college and university foodservice directors were appropriate for hospitals and to confirm content validity as described by Worthen, Borg, and White (1993). Minor wording changes, such as changing the term "university administrators" to "hospital administrators," were made.…”
Section: Questionnaire Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many university dining services are beginning to draw on the supply chain principles of restaurants and grocery stores that look to source their food stocks sustainably. This has been in large part due to student pressure on universities' administrations [56,57].…”
Section: Comparing Campus Operations Policiesmentioning
confidence: 99%
“…Stokes, Arendt, and Strohbehn (2014), in a study about foodservice employee's perceptions about F2S, found that school foodservice employee's perceived that getting support from parents and students were equally important, in implementing F2S programs (n = 199-211). In another study, customers were noted as important to influencing decisions to implement sustainable practices, such as local purchasing, in colleges and university foodservice (Chen, Arendt, & Gregoire, 2011). School FSDs indicated a strong willingness to try to procure using alternative methods, yet their actual ability to procure alternatively was weaker, possibly indicating a lack of capacity to change their process.…”
Section: Conclusion and Applicationsmentioning
confidence: 99%